Examining alcohol consumption with the theory of planned behaviour: Do health and alcohol knowledge play a role? - Hasking, Penelope; Schofield, L. (Routledge, 2014)
We used the theory of planned behaviour (TPB) to investigate factors associated with alcohol consumption among university students, and to examine whether general or alcohol-specific health knowledge acts as a moderator in the relationship between elements of the theory and drinking behaviour. Participants were 258 Australian undergraduate university students (79% female) who completed an online questionnaire, assessing the constructs of interest. The hypothesis that intentions and behaviour would be successfully predicted using the theory was generally supported. Little evidence for the moderating effect of knowledge on the TPB variables was observed, although both general and alcohol-specific health knowledge moderated the relationship between intentions and behaviours. Contrary to expectation, more accurate knowledge strengthened this relationship. Further work is necessary to investigate the role of knowledge in limiting alcohol-related harms.